The construction sector and economic growth in sub-Saharan Africa (revisited) - Lopes, Jorge (2020)
The relationship between a country’s level of construction activity and its stage of economic development has been the subject of study at the macroeconomic level for the last forty years or so. This study follows an earlier research that investigated the relationship between investment in construction and economic development in Sub-saharan Africa (SSA), and found that the share of construction in national economy follows an inverted U-shaped pattern of development. That is, it firstly increases in the early stages of development and ultimately tend to decline in the latest stages of economic development. The research is based on data acquired on 22 of the countries in SSA over the period 1990-2017 and the sample is split into two groups according to the proportion of the construction sector in total value added in the period 1990-1999. The results of the analysis of the development pattern of the construction industry in the two categories of countries tend to corroborate the results of the earlier work in what regards the evolutionary pattern of the middle-income economies in SSA.